Interaction between Brand and User: Daily Interface on Pinterest Inspiration Boards - Meire Soares Raslan, Eliane; Luiza Lima, Joice (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Social networks have become part of society's daily life and brands change the way of relating online. In this context, the profile of the Luisa Meirelles brand on the Pinterest Platform is analyzed from its posted inspiration boards. The production space of interactions between the brand and its users is related to the visual and daily interface of the brand in this virtual environment, increasing interactions and consumption with the potential consumers involved. The sharing of these images creates interactions between people from the mutual influence between electronic and social media, in front of this panel of ideas.